A comprehensive overview and recent advances on polyhydroxyalkanoates (PHA) production using various organic waste streams. (April 2021) - Ganesh Saratale, Rijuta; Cho, Si-Kyung; Dattatraya Saratale, Ganesh; Kadam, Avinash A.; Ghodake, Gajanan S.; Kumar, Manu; Naresh Bharagava, Ram; Kumar, Gopalakrishnan; Su Kim, Dong; Mulla, Sikandar I.; Seung Shin, Han
Graphical abstract: Highlights: Polyhydroxyalkanoates a potential biopolymer substitute for conventional plastics. Critically reviewed various waste streams for sustainable and inexpensive PHA production. Recent advances on fermentation strategies & synthetic biology for higher PHA production. Discussed PHA- nanocomposites and their application in various sectors. Future perspectives & technical challenges for efficient waste-bioplastic production addressed. Abstract: Polyhydroxyalkanoates (PHA) are appealing as an important alternative to replace synthetic plastics owing to its comparable physicochemical properties to that of synthetic plastics, and biodegradable and biocompatible nature. This review gives an inclusive overview of the current research activities dealing with PHA production by utilizing different waste fluxes generated from food, milk and sugar processing industries. Valorization of these waste fluxes makes the process cost effective and practically applicable. Recent advances in the approaches adopted for waste treatment, fermentation strategies, and genetic engineering can give insights to the researchers for future direction of waste to bioplastics production. Lastly, synthesis and application of PHA-nanocomposites, research and development challenges, future perspectives for sustainable and cost-effective PHB production are also discussed. In addition, the review addresses the useful information about the opportunities and confines associated with the sustainable PHA production using different waste streams and their evaluation for commercial implementation within a biorefinery.